Memorizing Bible Verses with the Association Method of Quantum Learning in Sunday School - Juanda Juanda; Handoko Noertjandranata; Sjanette Eveline; Surja Permana; Frederich Oscar Lontoh (Jurnal Didaskalia, 2019)
In the world of teaching, it takes a variety of creativity, so that students benefit from the learning process. The same thing happened in the Sunday School class held by the church. The core material is certainly from the Bible. This includes memorizing Bible verses from certain parts. Students are required to memorize the verses. Many face failure in the memorization process. They have difficulty remembering the verses. However, there is still an interesting method to make it easier for children to memorize Bible verses, namely by association methods found in quantum learning. The problem is whether the Sunday school teachers understood this association method? With descriptive research methods have found a solution that in the process of memorizing with this association method, can increase the number of verses memorized. This can be shown from the results of evaluations that have been carried out, there is an increase in the number of memorized verses that can be memorized by Sunday school students, which increases to 20 words or about 4%.